Seismic microzonation map of Penang Island - Aghdam, Nasim Sarrafi; Suhatril, Meldi; Hashim, Roslan; Kashani, Alireza (Patron Editore, 2018)
The Peninsula of Malaysia is situated at a distance of 350 km from the seismic zone of Sumatra fault. However, some ground motions are caused by the Sumatra Earthquake. According to the announcements by the Malaysian Metrological Department, the earthquake occurred near Sumatra on 2nd November 2002 with the magnitude of 7.4 had caused tremors in various parts of the Malaysian Peninsula including Penang Island. Penang Island is the most populous island city which is situated in the state of Penang with a rising population of 0.7 million people. Hence, the need for seismic hazard mitigation is evident. In this research, seismic microzonation maps presenting amplification and surface acceleration are plotted to produce a comprehensive microzonation model, to indicate the high risk earthquake areas for land use management. 24 boreholes were located and drilled for data collection. The collected data from boreholes and the bedrock motion obtained were calculated by NERA (Nonlinear Earthquake site Response Analysis), which had generated the surface acceleration and amplification needed for mapping. The results of this paper show the high seismic risk areas on eastern part of the Island that can be used in the planning of urban city infrastructure, which can recognize, control and prevent geological hazards.